Measurement, Analysis and Interpretation of Pressure/Flow Waves in Blood Vessels - Mynard, Jonathan P.; Kondiboyina, Avinash; Kowalski, Remi; Cheung, Michael M. H.; Smolich, Joseph J. (Frontiers in Physiology, 2020)
The optimal performance of the cardiovascular system, as well as the break-down of this performance with disease, both involve complex biomechanical interactions between the heart, conduit vascular networks and microvascular beds. ‘Wave analysis’ refers to a group of techniques that provide valuable insight into these interactions through scrutinizing the shape of blood pressure and flow/velocity waveforms. The aim of this review paper is to provide a comprehensive introduction to wave analysis, with a focus on key concepts and practical application rather than mathematical derivations. We begin with an overview of invasive and non-invasive measurement techniques that can be used to obtain the signals required for wave analysis. We then review the most widely-used wave analysis techniques: pulse wave analysis, wave separation and wave intensity analysis, including associated methods for estimating local wave speed or characteristic impedance which are required for decomposing waveforms into forward and backward wave components. This is followed by a discussion of the biomechanical phenomena that can generate waves and the processes that modulate wave amplitude, both of which are critical for interpreting measured wave patterns. Finally, we provide a brief update on several emerging techniques/concepts in the wave analysis field, namely wave potential and the reservoir-excess pressure approach.